The Tale of Si Kabayan Hayang Kawin: A Meaning Embodied in Oral Literature - Megan Asri Humaira (Indonesian Journal of Social Research (IJSR), 2020)
The fairy tale of Si Kabayan is a fairy tale in Sundanese society. Various fairy tales about Si Kabayan Save the meaning that can be taken by the community, especially the fairy tale of Si Kabayan Hayang Kawin. This fairy tale is examined in order to know the meaning contained within it using qualitative methods of descriptive. This fairy tale serves as an educational tool, consolation or entertainment, and a means of wearers enact social norms. As for the meaning of the fairy tale Si Kabayan Hayang Kawin, it is obvious that Kabayan's insinuation of one trait of society is lazy.